PERIAPICAL SURGERY. EPIDEMIOLOGY, INDICATIONS AND CONTRAINDICATIONS. REVIEW - Bogdan Krastev; Ivan Filipov (Peytchinski Publishing, 2020)
Periapical endodontic surgery (apical osteotomy, apicoectomy, apicectomy, root resection), aims at the treatment of apical periodontitis, after exhaustion of the possibilities of orthograde endodontics. Surgery is an essential part of endodontics and helps us retain natural teeth as long as possible. Not all periapical lesions are of true endodontic origin and can be treated nonsurgically. With the development of new instruments and techniques, the indications for performing the procedure have changed. Clinicians should know all peculiarities when faced with patients with a different medical history or anatomical variations. They should be prepared to cope with intra/post operative pain and complications. In this review are presented epidemiology, ways of treatment of periapical lesions, advantages and disadvantages, indications and contraindications of performing this procedure, peculiarities with different patients, as well as methods of conducting it, based on the current literature.